Toksisitas beberapa kategori asap cair dari kayu kusambi dan tempurung kelapa menggunakan metode Brine Shrimp Lethality Test - Kasimir Sarifudin; Adytia Dwipatria de Gatas; Heru Christianto; Parera Parera (Media Sains, 2023)
This study aims to determine the level of toxicity in various categories of liquid smoke from kusambi wood and coconut shells. The liquid smoke produced from the pyrolysis of kusambi wood and coconut shells at ±400 ℃. Liquid smoke resulting from pyrolysis then distilled to achieve grade 3. Grade 3 liquid smoke filtered in zeolite and activated charcoal column to obtain grade 2 and  1 categories. The toxicity test was conducted using the BSLT method of 48-hour-old Artemia salina Leach shrimp larvae. The toxicity level of each liquid smoke was identified by the percentage of shrimp larvae mortality and determination of lethal concentration (LC50). Determination of total phenol content using a Shimadzu UV-Vis 1780 spectrophotometer. The results showed that toxicity of liquid smoke from the pyrolysis of kusambi wood and coconut shells is toxic, with LC50 <1000 ppm, while the Kusumbi wood and coconut shells liquid smoke from distillation processes, grade 2 and grade 1 are non-toxic, with the LC50 > 1000 ppm.